LEADER COMMUNICATION MODEL IN ENHANCING THE PERFORMANCES OF STAFFS IN THE POLICE SECTOR OFFICE OF SINABOY AT THE DISTRIC OF ROKAN HILIR - Sari, Hotna (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
The purpose of this study was to determine the pattern of leadership communication in improving employee performance at the Sinaboy Police, Rokan Hilir Regency. The research method used is descriptive qualitative with a population of 22 people. The sampling technique used is a proportional sample. The number of samples or informants in this study were 8 informants. Data was collected by conducting observations, interviews, documentation and reference searches. The data sources used are primary sources and secondary data sources. Data processing and analysis techniques go through three stages, namely: data reduction, data presentation and conclusion drawing. The results of this study indicate that the pattern of communication and message flow used in an effort to improve employee performance at the Sinaboy Posek, Rokan Hilir Regency is a structural pattern. The indicator of this communication pattern is the communication from top to bottom, horizontal communication and diagonal communication. Barriers to Leadership Communication on Employee Performance at the Sinaboy Posek, Rokan Hilir Regency are (a) Miss communication; namely errors in communication such as errors in conveying information from the head of service to employees and staff, (b) Semantic barriers are barriers that have ambiguous meanings, in communicating between managers and staff feedback is expected; and (c) Physical barriers. Physical barriers are very influential on communication because with this obstacle the information conveyed will not reach the recipient of the message.Keywords: Leader Communication Pattern, Employee Performance